2011
DOI: 10.13057/biodiv/d130107
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of endophytic fungi isolated from Dendrobium crumenatum Sw. (Pigeon orchid) and antimicrobial activity

Abstract: Mangunwardoyo W, Suciatmih, Gandjar I. 2012

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…This is the first report of the antifungal potential of endophytic fungi isolated from flowers of Dendrobium lindleyi . In relation to other species, Mangunwardoyo et al () reported that endophytic fungi were isolated from roots, bulbous parts, stems and leaves of Dendrobium crumenatum , and the endophytic fungi revealed that Fusarium nivale showed antimicroorganism activities against Candida albicans and Candida tropicalis .…”
Section: Discussionmentioning
confidence: 99%
“…This is the first report of the antifungal potential of endophytic fungi isolated from flowers of Dendrobium lindleyi . In relation to other species, Mangunwardoyo et al () reported that endophytic fungi were isolated from roots, bulbous parts, stems and leaves of Dendrobium crumenatum , and the endophytic fungi revealed that Fusarium nivale showed antimicroorganism activities against Candida albicans and Candida tropicalis .…”
Section: Discussionmentioning
confidence: 99%
“…could found as endophytic fungi in another plant. Fusarium nivale and Fusarium solani were found in Dendrobium crumenatum Sw. (Mangunwardoyo et al 2012). F. semitectum were found in Talinum paniculatum leaf (Hastuti et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The mitosporic fungi specifically the class of the Hyphomycota has been considered as the most predominant group in the majority of the plants colonized by the mycoendophytes, it is justified by a lot of studies (Seena and Sridhar 2004;Khan et al 2007;Mangunwardoyo et al 2012;Jena and Tayung 2013;Han et al 2013;Sharma and Kumar 2013;Shi et al 2013;Suciatmih and Rahmansyah 2013;D'souza and Bhat 2013). The nature of dominance of the ISSN 2166-0379 2020 Hyphomycetes can be assigned to their capacity to colonize their host quickly while producing abundant asexual spores (Jena and Tayung 2013).…”
Section: Discussionmentioning
confidence: 99%